Analysis of patients with severe acute respiratory syndrome belonging to a municipality in the south of Santa Catarina in the period from 2019 to 2022 (Research, Society and Development, 2023)
Objectives: To understand the profile of patients with severe acute respiratory syndrome in the municipality of Tubarão, Santa Catarina. Methods: A cross-sectional study was conducted, analyzing data from notifications and investigations of 3.295 severe acute respiratory syndrome cases, with data recorded and reported to the Notifiable Diseases Information System (SINAN), from january 2019 to june 2022. Results: Among the signs and symptoms presented by the patients, the most common were: Dyspnea (86.9%), Respiratory Distress (85.0%), and Oxygen Saturation < 95% (64,7%). Approximately 29.5% of patients were admitted to the ICU, and 48.4% received invasive ventilatory support. The most commonly associated comorbidity with the syndrome was Chronic Cardiovascular Disease, present in 44.2% of patients. Additionally, around 36% of patients progressed to death. Conclusion: Severe Acute Respiratory Syndrome is a condition with high mortality and a need for ventilatory support, invasive or non-invasive. It is significantly associated with the most prevalent comorbidities in the population, such as Diabetes Mellitus and Chronic Cardiovascular Disease. Therefore, research in these areas is crucial to encourage prevention and treatment measures, thereby reducing the costs associated with public health.